2015
DOI: 10.1002/hep.27318
|View full text |Cite
|
Sign up to set email alerts
|

Portal myofibroblasts promote vascular remodeling underlying cirrhosis formation through the release of microparticles

Abstract: Liver fibrosis expanding from portal tracts and vascular remodeling are determinant factors in the progression of liver diseases to cirrhosis. In the present study, we examined the potential contribution of portal myofibroblasts (PMFs) to the vascular changes leading to cirrhosis. The analyses of liver cells based on the transcriptome of rat PMFs, compared to hepatic stellate cell HSC‐derived myofibroblasts in culture, identified collagen, type XV, alpha 1 (COL15A1) as a marker of PMFs. Normal liver contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 48 publications
4
94
0
Order By: Relevance
“…In other studies, exosomes were capable of transducing Hedgehog signals (13). Microparticles have also been implicated in cirrhosis and portal hypertension, with evidence that such particles may contain the angiogenic molecule VEGF and other studies providing evidence that these particles can mediate hemodynamic disturbances associated with cirrhosis (50). Our study adds to these existing models not only by showing a role for exosomes in paracrine signaling relevant to cir-FIGURE 6.…”
Section: Discussionsupporting
confidence: 56%
“…In other studies, exosomes were capable of transducing Hedgehog signals (13). Microparticles have also been implicated in cirrhosis and portal hypertension, with evidence that such particles may contain the angiogenic molecule VEGF and other studies providing evidence that these particles can mediate hemodynamic disturbances associated with cirrhosis (50). Our study adds to these existing models not only by showing a role for exosomes in paracrine signaling relevant to cir-FIGURE 6.…”
Section: Discussionsupporting
confidence: 56%
“…3E). Additionally, the PF markers NTPDase2 ( Entpd2 ) and type XV collagen26 ( Col15a1 ) were significantly enriched in Thy1 MCs (Supporting Fig. S3A).…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis, periportal Thy1‐expressing cells stably expressed α‐SMA even at normal states, along with many other PF markers, such as elastin and NTPDase2. However, cells that line the vascular wall of the portal vein also express most, if not all, of the known PF markers18, 26 (Supporting Figs. S1B, S6B) and are the mesenchymal‐type cell population, thereby falling into the category of conventional PFs.…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhosis may induce a decrease of the MAP, mainly due to vasodilation of the splanchnic and peripheral vascular beds. Niederberger et al reported a halving of the systemic vascular resistance after 9-10 weeks of CCL 4 -intoxication in rats [24]. At that time, rats had already developed cirrhotic ascites.…”
Section: ) Circulatory Disordersmentioning
confidence: 99%
“…Eventually, normal liver tissue is replaced by diffuse fibrosis, vascularized ƒfibrotic septa, and regenerative nodules [2]. Previous studies have shown that the associated morphological reorganization of the hepatic architecture contributes to the increasing intrahepatic vascular resistance (IHVR), dysregulating liver perfusion [3,4].…”
Section: Introductionmentioning
confidence: 99%